Varicella-Zoster Virus and Ramsay Hunt Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
Fifty two children, aged 2 to 15 years, diagnosed with Ramsay Hunt syndrome (RHS) in a 20 year period between 1976 and 1996 are reported from the Facial Nerve Clinic, Ehime University Hospital, Japan.